Biosensors supporting healthcare in missions — expert consensus on the status of implementation in the military and future tasks - Rausch, Monika; Schaebler, Alexander; Scheid, Patrick Leander; Kowitz, Stefan; Düking, Peter; Sperlich, Billy; Küpper, Thomas (Health Promotion & Physical Activity, 2022)
The monitoring of physiological parameters using wearable (bio-) sensors of military personnel is a progressing process within the military environment. It sets high demands on such devices, in order to support healthcare and performance of the personnel. To get an ovierview of the current status of the use, the evaluation and the implementation in the military, in May 2021, the Multinational Medical Coordination Centre / European Medical Command has organized an expert workshop about ‘Biosensors Supporting Healthcare in Missions’. Three thematic clusters were addressed: ‘Human Performance and Readiness’; ‘Health and Medical Management Applications’ and ‘Ethical and Legal Aspects of the Use of Biosensors’.